The Development of STEM Mobile Learning Package Ecosystem (Jurnal Pendidikan IPA Indonesia, 2019)
This study aims to: develop and test the validity, legibility and effectiveness of STEM Mobile Learning Package ecosystems on students’ science and technology literacy using R D research design. STEM Mobile Learning Package was validated by media experts and material experts. The level of legibility is measured by questionnaire through the results of a small-scale trial of a Biology student class. The effectiveness of the application was measured in wide-scale test for biology and natural science students. Data were analyzed using descriptive quantitative.The results showed the the validity on learning package from experts showed valid in 83,6%. Some revisions are needed especially on video aspect which will be better filled with not only text but also voice. Base on data collected from 47 students who have completely filled 12 statements in questionnaire, about 78,7% students stated they could understand the questions very well. Most of students (97,8%) agreed that the use of STEM enhanced their science literacy. Percentage of students that agreed on 12 statements ranged from 74,5% to 100%. Thus those result indicated a high level of legibility Although learning packages can be studied independently, certain topics still requiredto be directly discussed. This learning package is effective on student scientific literacy ranging from 64.6 to 98.6. While the highest achievement of student technology literacy is 92 with an average of 70.32. This study concludes that STEM Mobile Learning Package Ecosystem has good validity and legibility, as well as effective on students’ science and technology literacy.